The Socio-cultural Variables Influencing Pakistan’s Perception of the COVID-19 Vaccine - ALI, AHMAD; NAEEM, MUHAMMAD; MUSTAFA, GHULAM; AKRAM, SUFIA; SHOUKAT, AYESHA; HANIF, JAVERIA; KHAN, SEMA; IMTIAZ, AYESHA; MUHAMMAD AZAM, SHEIKH; NAQVI, SAHRISH; AHMAD, GHAFOOR; IMRAN, MUHAMMAD; et al. (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: The present study investigates the perceptions of students and the general public about COVID-19 vaccination in Pakistan. Socio-cultural variables such as lifestyle, buying habits, education, age, gender, religion, beliefs, values, demographics, social classes, sexuality, and attitudes affect people's perceptions and lead them to think differently. The survey aims to create a discourse around the socio-cultural variables of COVID-19 vaccination and inform future policies and practices to promote more vaccination. Methodology: A survey was conducted at the public and private universities in Pakistan using a Google Form questionnaire. The responses of 304 participants were analyzed to assess their perception of the COVID-19 vaccination. The findings indicate that a significant proportion of students and the general public in Pakistan hold positive opinions regarding the COVID-19 vaccination. Results: The results of the university students show that more than half of the respondents (66%) were confident in the COVID- 19 vaccine, and 11.2% of the respondents were not confident in the COVID-19 vaccine. And 22.9% of respondents were hesitant about getting the vaccination. At the same time, the results from the general public show that more than half (53%) of respondents were confident, but that is less than the university student’s confident percent. About 23.8% of the general public were not confident. Practical implication: The study suggests that public health campaigns should target different demographics, particularly women, and age-specific strategies like vaccine education, social media, and community outreach programs to boost vaccine acceptance and public health. Conclusion: Through this, it is proven that socio-cultural variables like education and more have influenced people’s perceptions of the COVID-19 vaccination because university students were more confident as compared to the general public. In this way, all socio-cultural variables influence the perceptions of people. As a result, governments and commercial groups all over the world have introduced policies to encourage or coerce vaccination.